Efficacy and safety of drug-coated balloon combined with cutting balloon for side branch of true coronary bifurcation lesions: Study protocol for a multicenter, prospective, randomized controlled trial - Wu, Haoyu; Deng, Jizhao; Liang, Lei; Lei, Xinjun; Yao, Xiaowei; Han, Wenqi; Chen, Haichao; Shou, Xiling (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary bifurcation lesions are common of percutaneous coronary intervention (PCI), and the optimal interventional therapy strategy is still a matter of debate and remains a challenge for interventional cardiologists. The provisional stenting technique is still a preferred method for most bifurcation lesions, but restenosis of the side branch (SB) occurs in approximately 17–19% of cases. Therefore, the dilemma of reducing SB restenosis still exists, and further research on strategies to reduce restenosis for SB is necessary. Drug-coated balloon (DCB) can reduce clinical events in small vessel disease and in-stent restenosis. The efficacy and safety of DCB for SB of true coronary bifurcation lesions have not been fully investigated. A randomized comparison of DCB combined with cutting balloon angioplasty vs. cutting balloon angioplasty for SB has never been published. Methods and design The purpose of this study is to explore the superiority of DCB combined with cutting balloon vs. cutting balloon angioplasty for SB after main vessel (MV) drug-eluting stent implantation of true coronary bifurcation lesions. This study is a multicenter, prospective, randomized controlled trial including 140 patients with true coronary bifurcation lesions. Patients will be randomized in a 1:1 manner to receive either DCB combined with cutting balloon or cutting balloon angioplasty for SB after MV drug-eluting stent implantation. The primary endpoint is the evaluation of late lumen loss (LLL) of SB at the 9-month follow-up. The secondary endpoints include procedural success during initial hospitalization, LLL of MV at the 9-month follow-up, binary angiographic restenosis in MV and SB at the 9-month follow-up, the proportion of patients with a final post-PCI quantitative flow ratio result ≤ 0.80 for SB at the 9-month follow-up, and major adverse cardiac events during the 24-month follow-up. Conclusions This clinical trial will provide evidence as to whether DCB combined with cutting balloon for SB of true coronary bifurcation lesions is a superior treatment approach. Trial Registration Number ChiCTR2000040475. Dissemination The results of this clinical trial will be published in a peer-reviewed journal.